PENERAPAN TERUMBU BUATAN (Aritificial Reef) DI PERAIRAN DESA RUTONG DALAM UPAYA REHABILITASI EKOSISITEM TERUMBU KARANG DAN PENINGKATAN USAHA PENANGKAPAN - Hukubun, Ronald Darlly; Rijoly, Frederik; Lokollo, Frijona F (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2022)
Application of artificial reefs in the waters of the Village Rutong is very well in supporting the rehabilitation of coral reefs that have been under pressure especially for reef fish resources. Methods used in these activities is the application of methods Ipteks Education through the delivery of material through the method of information about activities of the rehabilitation efforts of coral reef ecosystems to the target audience of the follow through artificial reef technology, and the training method is through the implementation of the manufacturing activities of coral artificial, haunted, and raft. Making the basic material of artificial reefs is a used car tires tied to form a triangle tires. Monitoring activities carried out 2 months after the splashdown in various types of fish that have used loopholes and surface car tires as well as a shelter looking for food. This continued to be held as ecological processes that will occur so that the initial function of artificial reefs that will serve as a fish nestt; and can be rehabilitated reef ecosystems that have been damaged will be realized